Does Hearing Thresholds Vary Across Different Blood Groups? - Sarve, Archana Rai; K., Megha; Hem, Devika (Journal of Health and Allied Sciences NU, 2019)
The current study aimed at identifying the relationship between the blood group and hearing thresholds. The objective of the study was to identify if there is a difference in the pure tone audiometric thresholds of individuals with different blood groups, and to identify if there is a difference between pure tone audiometric thresholds of males and females of the same blood group. A prospective study was performed involving 80 normal hearing individuals between the age of 18 and 40 years. All participants included in the study had normal hearing (< 25 dBHL) and were Rh+. Participants complaining or giving indications of any kind of cochlear or retrocochlear pathological conditions were excluded from the study. Participants were grouped based on their blood groups. Each group consisted of 20 participants. Thresholds were established for frequencies ranging from 125 Hz to 20 KHz. Descriptive statistical analysis was done for mean and standard deviation. Bonferroni post hoc analysis was carried out for multiple comparisons, and the results revealed that there was no statistically significant difference in thresholds observed among different blood groups.
Keywords: behavioral threshold; pure tone audiometry; ABO classification; blood group